Предмет: Алгебра,
автор: даданет
Помогите с уравнением (а), пожалуйста
Приложения:
Ответы
Автор ответа:
0
(6-х)(6+х)-(х-11)=36
36+6х-6х-х²-х+11=36
36-х²-х+11=36
-х²-х+11=0
х²+х-11=0
D=1²-4•(-11)=√45 = 3√5
x1 = -1 - 3√5 / 2
x2 = -1 + 3√5 / 2
36+6х-6х-х²-х+11=36
36-х²-х+11=36
-х²-х+11=0
х²+х-11=0
D=1²-4•(-11)=√45 = 3√5
x1 = -1 - 3√5 / 2
x2 = -1 + 3√5 / 2
Похожие вопросы
Предмет: Обществознание,
автор: kateivanova2008
Предмет: Физика,
автор: Pwiuteeu
Предмет: Русский язык,
автор: Karinafox1712
Предмет: История,
автор: валерия190
Предмет: Биология,
автор: 79194326675